2022
DOI: 10.7759/cureus.27849
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Atrial Fibrillation on Patients With Inflammatory Bowel Disease Admitted for Colectomy

Abstract: IntroductionInflammatory bowel disease (IBD) is a chronic, relapsing, inflammatory disorder of the gastrointestinal tract. Patients with IBD may undergo a segmental or total colectomy, depending upon the extent of the disease. It is estimated that approximately 20 to 30 percent of patients with advanced ulcerative colitis will eventually require surgical resection. The incidence and prevalence of Atrial Fibrillation (AF) are increasing globally. There is plausible evidence linking inflammation to the initiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…It was indicated that IBD patients with atrial fibrillation had a longer mean length of stay, greater total hospital charge, and an in-hospital mortality rate after the colectomy. Moreover, they had a greater risk of requiring mechanical ventilation, developing cardiac arrest, and ICU admission [25]. Interestingly, Tilly et al examined the relationship between autoimmune diseases and new-onset atrial fibrillation in a large UK population [28].…”
Section: Inflammatory Bowel Disease and Atrial Fibrillationmentioning
confidence: 99%
See 1 more Smart Citation
“…It was indicated that IBD patients with atrial fibrillation had a longer mean length of stay, greater total hospital charge, and an in-hospital mortality rate after the colectomy. Moreover, they had a greater risk of requiring mechanical ventilation, developing cardiac arrest, and ICU admission [25]. Interestingly, Tilly et al examined the relationship between autoimmune diseases and new-onset atrial fibrillation in a large UK population [28].…”
Section: Inflammatory Bowel Disease and Atrial Fibrillationmentioning
confidence: 99%
“…In a more recent study, Mahfouz et al . [25] examined the impact of atrial fibrillation in patients with IBD that underwent colectomy. In this study, the IBD patients with atrial fibrillation were older (71 vs 49 years of age) and they had more comorbidities such as hypertension, diabetes, congestive heart failure, chronic kidney disease, COPD, and coronary artery disease.…”
Section: Inflammatory Bowel Disease and Atrial Fibrillationmentioning
confidence: 99%